2020
DOI: 10.1177/1479973120928103
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of sleep-disordered breathing in Northwest Russia: The ARKHsleep study

Abstract: Sleep-disordered breathing (SDB) is a chronic condition characterized by repeated breathing pauses during sleep. The reported prevalence of SDB in the general population has increased over time. Furthermore, in the literature, a distinction is made between SDB, obstructive sleep apnea (OSA), and “OSA syndrome” (OSAS). Patients with SDB are at increased risk of comorbid cardiovascular diseases (CVDs). The aim of the ARKHsleep study was to assess the prevalence of SDB in general and of OSA and OSAS in particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 51 publications
0
11
0
1
Order By: Relevance
“…A recent study found that out of 38,000 Russian citizens (aged 30–70 years), 48.9% suffered from an AHI (Apnea-Hipopnea Index) ≥ 5, 18.1% from an AHI ≥ 15 and 4.5% from an AHI ≥ 30 [ 4 ]. In 2020, Peñafiel et al observed 205 people (aged between 18–84 years) undergoing overnight respiratory polygraphy and they found a prevalence of 49% AHI ≥ 5 and 16% AHI ≥ 15 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that out of 38,000 Russian citizens (aged 30–70 years), 48.9% suffered from an AHI (Apnea-Hipopnea Index) ≥ 5, 18.1% from an AHI ≥ 15 and 4.5% from an AHI ≥ 30 [ 4 ]. In 2020, Peñafiel et al observed 205 people (aged between 18–84 years) undergoing overnight respiratory polygraphy and they found a prevalence of 49% AHI ≥ 5 and 16% AHI ≥ 15 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a common sleep disorder disease, OSAS is characterized by sudden pauses of breathing during sleep (Khokhrina et al 2020 ). Resulting from repeated obstructions of the pharyngeal airway, CIH is a cardinal feature of OSAS, which induces degrease of cognitive performance (Li et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…OSAS is a disease that is common among middle-aged and older adults, and it affects 26% of individuals between the ages of 30 and 70 in the USA [ 4 ]. In Russian citizens, this rate is 48.9% [ 5 ]. In 2020, S aldías P eñafiel et al .…”
Section: Introductionmentioning
confidence: 99%